Vertebra of a Bowhead whale (Balaena mysticetus) in Late Wisconsinan deglacial marine sediments, Trout River, Newfoundland, and local late-glacial sea-level change - Brookes, Ian (Géographie physique et Quaternaire, 2007)
AbstractThis note reports the geological contexts and radiocarbon and calibrated ages of whalebone and bivalve recovered from emerged deglacial marine sediments at Trout River, Newfoundland (49°28.6’ N, 58°07’ W). The rate of sea-level fall is calculated for the first deglacial millennium, and discrepancies are noted between calibrated ages of bone and shell.